Selective COX-2 inhibitor versus non-selective COX-2 inhibitor for the prevention of heterotopic ossification after total hip arthroplasty: A meta-analysis. Issue 31 (August 2018) - Zhu, Xi-Tian; Chen, Lei; Lin, Jian-Hua
Abstract: Background: Whether selective non-steroidal anti-inflammatory drugs (NSAIDs) has equally efficacy with non-selective NSAIDs in preventing heterotopic ossification (HO) after total hip arthroplasty (THA) was controversial. The purpose of this meta-analysis was to assess the efficacy and safety of selective NSAID versus non-selective NSAIDs for the prevention of HO after THA. Methods: PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Web of Science, Google Search Engine, and China National Knowledge Infrastructure databases was searched for randomized controlled trials (RCTs) were comparing selective NSAID versus non-selective NSAIDs for preventing HO after THA. The primary outcomes were overall HO incidence, Brooker classification HO incidence, gastrointestinal side effects, the occurrence of excessive bleeding and discontinuation caused by gastrointestinal side effects (DGSE). Data were analyzed using Stata 12.0. Results: A total of 8 RCTs involving 1636 patients were included in the meta-analysis. There was no significant difference between the nonselective NSAIDs group and the selective NSAIDs group in the overall incidence of HO (relative risk, RR = 0.91, 95% confidence intervals, CI 0.78–1.06, P  = .203), Brooker I HO (RR = 1.02, 95% CI 0.85–1.23, P  = .794), Brooker II HO (RR = 1.00, 95% CI 0.66–1.52, P  = .996). Brooker III HO (RR = 0.98, 95% CI 0.37–2.62, P  = .971). And the occurrence of excessive bleeding (RR = 0.67, 95% CI 0.24–1.92, P  = .458). The selective NSAIDs group was associated with a significant decrease in gastrointestinal side effects (RR = 0.35, 95% CI 0.18–0.71, P  = .004) and discontinuation caused by gastrointestinal side effects compared with the nonselective NSAIDs group (RR = 0.28, 95% CI 0.11–0.66, P  = .004). Conclusion: The available evidence indicates selective NSAIDs were as effective as non-selective NSAIDs in preventing HO after THA. And selective NSAIDs were associated with less gastrointestinal side effects than non-selective NSAIDs. Considering the limitation of current meta-analysis, more RCTs need to identify the optimal NSAIDs drug for HO after THA. Abstract : Supplemental Digital Content is available in the text